2020
DOI: 10.1002/jbt.22479
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotective effects of montelukast, a selective leukotriene CysLT1 receptor antagonist, against nephrotoxicity induced by gamma radiation in mice

Abstract: Purpose In this study, we evaluated the renal protective effects of montelukast (MLK) against ionizing radiation (IR) induced nephrotoxicity in mice. Materials and Methods Radioprotective effects of MLK were assessed by biochemical analysis including measurements of kidney malondialdehyde (MDA), reduced glutathione (GSH), and serum creatinine and urea levels. Besides, for further evaluation of protective effects of MLK on renal system, 99mTc‐dimercaptosuccinic acid (DMSA) has been applied. The total antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…In our study, both carvacrol, thymol, and their combination alleviated renal oxidative stress induced by γ-irradiation, which is consistent with the results of recent studies reporting the radioprotective effects of thymol and carvacrol through an antioxidant mechanism [29,32,35]. In this context, studies have documented the mitigation of radiation-induced oxidative stress when the antioxidative substances were administrated before γ-irradiation, supporting our findings [59,60].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, both carvacrol, thymol, and their combination alleviated renal oxidative stress induced by γ-irradiation, which is consistent with the results of recent studies reporting the radioprotective effects of thymol and carvacrol through an antioxidant mechanism [29,32,35]. In this context, studies have documented the mitigation of radiation-induced oxidative stress when the antioxidative substances were administrated before γ-irradiation, supporting our findings [59,60].…”
Section: Discussionsupporting
confidence: 92%
“…Even in those cells which did not die from the acute DNA damage, mis-repaired DSBs might induce cell death or cellular senescence and inflammation in the long term [ 67 , 68 ]. Although there is scarcity of data on active inflammation in RN, the inhibition of the renal expressions of NF-κB and TNF-α was found to be involved in the protective effect of montelukast against RN in a dose-dependent manner [ 60 , 69 ]. In our study, the administration of carvacrol or thymol and their combination substantially alleviated the renal inflammation and apoptosis, which is consistent with the results of recent studies [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is critical to examine the mechanism of IR-induced renal injury and look for effective preventive measures against it. Studies have shown that radiation, including 60 Co-γ rays ( 22 , 23 ), 8-Gy γ rays ( 24 ), cesium-137 rays ( 25 , 26 ), and X-rays ( 27 ), can cause the impairment of renal function and pathological changes. In our study, compared with the control group, the radiation group exhibited significantly increased oxidative damage of the kidneys (increased malondialdehyde, hydrogen peroxide, and advanced oxidation protein products levels; decreased hydrogen peroxide level and total antioxidant capacity), abnormal renal function indices (increased SCr, BUN, cystatin C, N-Gal, and kidney injury molecule-1 levels), and pathological changes of the kidneys (atrophic and fibrotic glomeruli, extensive degeneration and necrosis of the renal tubular epithelial cells, disappearance of brush edges, and vascular congestion).…”
Section: Discussionmentioning
confidence: 99%
“…MLK has the potential to be used as a renal protective agent against gamma radiation in radiotherapy, per the findings of Hormati et al . 76 . A higher level of MDA was detected in IR-treated rats, which is a result of the oxidative stress induced by IR in the kidney.…”
Section: Discussionmentioning
confidence: 99%